Consistent Prebiotic Effects of Carrot RG-I on the Gut Microbiota of Four Human Adult Donors in the SHIME® Model despite Baseline Individual Variability - Pieter Van den Abbeele; Cindy Duysburgh; Ilse Cleenwerck; Ruud Albers; Massimo Marzorati; Annick Mercenier (Microorganisms, 2021)
The human gut microbiome is currently recognized to play a vital role in human biology and development, with diet as a major modulator. Therefore, novel indigestible polysaccharides that confer a health benefit upon their fermentation by the microbiome are under investigation. Based on the recently demonstrated prebiotic potential of a carrot-derived pectin extract enriched for rhamnogalacturonan I (cRG-I), the current study aimed to assess the impact of cRG-I upon repeated administration using the M-SHIME technology (3 weeks at 3g cRG-I/d). Consistent effects across four simulated adult donors included enhanced levels of acetate (+21.1 mM), propionate (+17.6 mM), and to a lesser extent butyrate (+4.1 mM), coinciding with a marked increase of OTUs related to Bacteroides dorei and Prevotella species with versatile enzymatic potential likely allowing them to serve as primary degraders of cRG-I. These Bacteroidetes members are able to produce succinate, explaining the consistent increase of an OTU related to the succinate-converting Phascolarctobacterium faecium (+0.47 log10(cells/mL)). While the Bifidobacteriaceae family remained unaffected, a specific OTU related to Bifidobacterium longum increased significantly upon cRG-I treatment (+1.32 log10(cells/mL)). Additional monoculture experiments suggested that Bifidobacterium species are unable to ferment cRG-I structures as such and that B. longum probably feeds on arabinan and galactan side chains of cRG-I, released by aforementioned Bacteroidetes members. Overall, this study confirms the prebiotic potential of cRG-I and additionally highlights the marked consistency of the microbial changes observed across simulated subjects, suggesting the involvement of a specialized consortium in cRG-I fermentation by the human gut microbiome.